Tryptophan: A Rheostat of Cancer Immune Escape Mediated by Immunosuppressive Enzymes IDO1 and TDO - Kim, Minah; Tomek, Petr (Frontiers in Immunology, 2021)
Blockade of the immunosuppressive tryptophan catabolism mediated by indoleamine 2,3-dioxygenase 1 (IDO1) and tryptophan 2,3-dioxygenase (TDO) holds enormous promise for sensitising cancer patients to immune checkpoint blockade. Yet, only IDO1 inhibitors had entered clinical trials so far, and those agents have generated disappointing clinical results. Improved understanding of the immunosuppressive mechanism mediated by tryptophan catabolism is likely to optimise therapeutic strategies to block this pathway. The immunosuppressive role of tryptophan metabolite kynurenine is becoming increasingly clear, but it remains a mystery if tryptophan exerts functions beyond serving as a precursor for kynurenine. Here we hypothesise that tryptophan acts as a rheostat of kynurenine-mediated immunosuppression by competing with kynurenine for entry into immune T-cells through the amino acid transporter called System L. This hypothesis stems from the observations that elevated tryptophan levels in TDO-knockout mice relieve immunosuppression instigated by IDO1, and that the vacancy of System L transporter modulates kynurenine entry into CD4+ T-cells. This hypothesis has two potential therapeutic implications. Firstly, potent TDO inhibitors are expected to indirectly inhibit IDO1 hence development of TDO inhibitors is favoured to IDO1-selective and dual IDO1/TDO inhibitors. Secondly, oral supplementation with System L substrates such as leucine represents a novel potential therapeutic modality to restrain the immunosuppressive kynurenine and restore anti-tumour immunity.